Stability analysis and numerical simulation of SEIR model for pandemic COVID-19 spread in Indonesia. (October 2020) - Annas, Suwardi; Isbar Pratama, Muh.; Rifandi, Muh.; Sanusi, Wahidah; Side, Syafruddin
Highlights: Mathematical model for Covid19. SEIR model for Covid19. Covid19 in Indonesia. Numerical solution of SEIR model. Abstract: The Aim of this research is construct the SEIR model for COVID-19, Stability Analysis and numerical simulation of the SEIR model on the spread of COVID-19. The method used to construct the model is the SEIR model by considering vaccination and isolation factors as model parameters, the analysis of the model uses the generation matrix method to obtain the basic reproduction numbers and the global stability of the COVID-19 distribution model. Numerical simulation models use secondary data on the number of COVID-19 cases in Indonesia. The results obtained are the SEIR model for COVID-19; model analysis yields global stability from the spread of COVID-19; The results of the analysis also provide information if no vaccine, Indonesia is endemic COVID-19. Then the simulation results provide a prediction picture of the number of COVID-19 in Indonesia in the following days, the simulation results also show that the vaccine can accelerate COVID-19 healing and maximum isolation can slow the spread of COVID-19. The results obtained can be used as a reference for early prevention of the spread of COVID-19 in Indonesia